Given equation: 7p - 3 = 3p + 8
⇒ 7p – 3p = 8 + 3 (Transposing 3p to LHS and 3 to RHS)
4p = 11
⇒ p = (Transposing 4 to RHS)
∴ The solution of 7p - 3 = 3p + 8 is p = .
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :